(untitled) (Circe de clásicos y modernos, 2021)
The question of the basis of linguistic signifi-cance is raised for the first time in Plato’s Cratylus, in the context of the opposition between nature (φύσις) and convention (νόμος), on which later debate about the matter was also based. This work presents an over-view of the most important theoretical aspects of the arguments of the naturalist and conventionalist theses as presented and defended in Cratylus and in other texts of the Ancient tradition, and outlines a typology of the varieties of both positions as offered in that tradition.